PERBEDAAN HASIL BELAJAR FISIKA SISWA YANG DIAJAR DENGAN MODEL CONTEXTUAL TEACHING AND LEARNING DENGAN MODEL PEMBELAJARAN KONVENSIONAL DI SMAS ADVENT 1 MEDAN - Dedi Holden Simbolon (JURNAL CURERE, 2022)
This study aims to determine the differences in students' physics learning outcomes who were taught using the Contextual Teaching and Learning model with the conventional learning model for class XI of SMA Swasta Advent 1 Medan. This type of research is an experimental research with a pretest-posttest group design. The population in this study were all students of SMA Advent 1 Medan. The sampling technique was carried out randomly (Cluster random sampling), namely class XI-1 as an experimental class taught using the Contextual Teaching and Learning model and class XI-2 as a control class taught using a conventional learning model. Each class consists of 32 people. The instrument of this research is a multiple choice test of 20 items with 5 choices, the instrument is first tested on students outside the sample to determine the validity, reliability, distinguishing power and level of difficulty of the questions. From the data analysis, the average pretest value for the experimental class was 45.78 with a standard deviation of 6.67 and the posttest average value was 85.15 with a standard deviation of 5.63, while in the control class, the pretest average value was 52.26 with a standard deviation of 12.32 and the posttest average value. 68.21 with a standard deviation of 7.12. Before testing the hypothesis, the normality and homogeneity of the data were first tested. From the results of the preliminary test, it was found that the two data came from a population that was normally distributed and homogeneous. The results of hypothesis testing using the t-test obtained tcount = 4.36 > ttable = 2.002 so that it can be concluded that there is a significant difference in the use of Contextual Teaching and Learning models on student physics learning outcomes in class XI SMA Swasta Advent 1 Medan.